Common Themes and Unintended Consequences in Class Action Reform - Francis E. McGovern (Washington University Law Quarterly, 2005)
The reform pendulum has been swinging in the direction of limiting the scope and flexibility of the class action procedural device. The Private Securities Litigation Reform Act (PSLRA), the Securities Litigation Uniform Standards Act (SLUSA), the Class Action Fairness Act (CAFA), Federal Rule of Civil Procedure 23 (Rule 23), various state statutes and rules, and a variety of state and U.S. Supreme Court decisions have included significant efforts to make class actions look more like traditional one-on-one litigation. These efforts have focused on five overlapping areas: public transparency, client control and attorney selection, attorney fees, suit selection, and an increased judicial role. At the same time, however, these reforms have generated unintended consequences that have the potential for creating new problems or undercutting the efficacy of the reforms themselves.
Keywords: Class actions (Civil procedure); Securities; Class action reform; Class action lawsuits; Lawyers' fees; United States